ELASTIC ELECTRON–ATOM TOTAL SCATTERING CROSS SECTIONS FOR THE ALKALINE EARTH METALS (FUDMA JOURNAL OF SCIENCES, 2023)
Total Cross-Sections (TCS) of elastic electron-atom scattering for the Alkaline Earth Metals Beryllium (Be), Magnesium (Mg), Calcium (Ca), Strontium (Sr), Barium (Ba) and Radium (Ra) are presented. The computed TCS were calculated using Born, Eikonal and the Optical Theorem approximation methods with the Lenz-Jensen potential, at electron incident energies between 1 to 1000 eV.  Results obtained are in good agreement with experimental TCS data
Keywords: Total Cross-Section, elastic scattering, alkaline earth metals, Optical theorem, Born approximation, Eikonal approximation